Determinan Kinerja Karyawan Bank Syariah - Rosyati, Rosyati; Damajanti, Anita; Karim, Abdul (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
The purpose of this conducted research was to test empirically how much influence the variables of education, organizational culture, work wages, work motivation have on employee performance variables. The research was conducted at Bank Jateng Syariah. The form of the research is quantitative research, using multiple linear regression analysis. Previously carried out model tests and statistical tests assisted by the SPSS 25 program. The number of respondents in this study were 60 respondents taken by purposive sampling method. Employees who are used as respondents must be permanent employees who work as front liners. The results showed that the higher the education, organizational culture, wages and work motivation, the higher the employee performance has the potential. In terms of significance, only education and work motivation show significant effects. Even though this study did not experience significant obstacles and the research model also showed feasibility, further research could still be carried out. Subsequent research can add more research variables.